Detailed pathological analysis of the advancing edge of the tumour can effectively stratify clinical T4b colorectal cancer patients. Issue 6 (1st April 2019) - Kim, So‐Woon; Kim, Jiyoon; Hong, Seung‐Mo; Yoon, Yong Sik; Park, In Ja; Yu, Chang Sik; Kim, Jihun
Abstract: Aims: Pathological staging of colorectal cancers (CRCs) that involve adhesion to adjacent organs (clinical stages T4b, cT4b) is sometimes difficult because the morphology of the invasive front varies. To resolve this issue, we reviewed 492 surgically resected CRC samples, comprising 96 cT4b tumours and, for comparison, 335 typical pathological stages (p) T3 and 61 pT4a tumours. Methods and results: Cases were subdivided into four groups according to the presence or absence of microscopic tumour invasion into the muscular wall of the adjacent organs and peritumoral abscess along invasive front. Those that directly invaded the wall of the adjacent organs without peritumoral abscess were associated with a significantly worse overall (OS) and recurrence‐free survival (RFS) than the other three types of cT4b tumours. Those with peritumoral abscess showed similar prognosis to typical pT3 tumours, even when the advancing edge of the tumour invaded the wall of adjacent organs (staged as pT4b). Tumours showing fibrous adhesions without tumour cell invasion into the muscular wall of the adjacent organs showed a similar prognosis to typical pT3 tumours and showed a better prognosis than pT4a tumours. Conclusion: Only CRCs with tumour cell invasion into the muscular wall of the adjacent organs should be classified as pT4b, and it might be better to avoid 'the presence of tumour cells in fibrous adhesion' to define pathological T4b CRCs. In addition, the presence of a peritumoral abscess should be recorded as a predictor of better prognosis.